Analisis Perbandingan Motif Geguritan Rajapala dengan Cerita Jaka Tarub dalam Babad Tanah Jawi - Hindrawan, Bayu; Ngurah Sulibra, I Ketut (Humanis; Vol 25 No 1 (2021), 2021)
This study examines the Geguritan Rajapala, from Bali with the story of Jaka Tarub, from Central Java. The purpose of this study is to find out the structure and motives of anything that builds between the two literature work, and how is the relations between Geguritan Rajapala with the story of Jaka Tarub within Babad Tanah Jawi. In this study uses structural theory and a Finnish comporative literary approach. This research method and technique uses the listening method, assisted with written and translation technique. While the data analysis stage uses qualitative methods, namely research that is descriptive and tends to use analysis and assisted with historical comparative technique, that is a technique carried out with aim of reconstruction and tentative mapping of literary kinship patterns with evidence based on types and motives. next one, the stage of presenting the results of data anlysis using informal methods assisted with deductive inductive technique. As for the results that can be obtained from this research are, knowing the structure that builds between the Geguritan Rajapala with the story of Jaka Tarub and knowing the motives contained therein. Based on these motives, the literary patterns of kinship can be mapped.